The Effect of Earnings Management and Dividend Policy on Company Performance: The Moderating Role of Corporate Governance Quality - Widiyati, Dira Ayu; Wijayati, Fitri Laela (Universitas Muhammadiyah Surakarta, 2025)
This study was conducted to determine the effect of earnings management and dividend policy on company performance with the quality of corporate governance as moderation in energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022. This study uses quantitative methods with a population of 38 companies and a sample of 190 observation data. The results of this study indicate that earnings management has no significant effect on company performance, dividend policy has no significant effect on company performance, and the quality of corporate governance, which is used as a moderating variable, cannot moderate earnings management and dividend policy.